Admission policy of students at Faculties of Education in Libyan Arab: evaluation study - Eman A. Shihob; Nik Mohd. Rahimi Nik Yusoff; Kamarulzaman Abdul Ghani; Kaseh Abu Bakar (Faculty of Education, Universiti Kebangsaan Malaysia, 2011)
This study is aimed to identify the student’s admission policy at the Faculties of Education in Libyan. The researcher was applied the descriptive - analytical approach, due to its relevance to the objectives of the study. The total size of the population for the study was (4048), from which a representative sample of (464) is chosen. A questionnaire, which is one of the descriptive approach tools, is used in this study. Due to the lack of a ready-in-hand questionnaire the researchers was prepared and built a questionnaire, and conducted validity and reliability of the tool. The researchers used appropriate statistical methods of frequencies, percentages, standard deviations, arithmetic means, and evaluation estimates. The study found that the paragraphs of the student’s admission were obtained average and weak evaluation estimates, which is an indication of the weakness of the admission policy in the Faculties of Education in Libyan. In addition, the study revealed that the programs and policies of the student’s admission were not implemented. Thus, the researchers put forwards a set of recommendations, among which, they recommended to choose and select the best of the applicants, who are willing to practice teaching, besides attracting the most intelligent, knowledge, and skilled applicants. This is can be achieved by activating the role of the personal interview and the necessity to pass this interview. This is in order to ensure a good appearance and strong personality of the applicant, besides the mental and intellectual integrity of the applicant. Moreover, it is also recommended to set high marks and percentage rates of success in high schools, which cannot be dispensed as a prerequisite requirement for admission policy. As well, the allocation of special committees for admission in the Faculties of Education and the follow-up procedures of registration and the choice of the specializations, and to put a studied plans to a link between the need for certain disciplines and the absorptive capacities of the Faculties.